1996
DOI: 10.1093/oxfordjournals.humrep.a019378
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of blood flow impedance in the uterine arteries of infertile women with electro-acupuncture

Abstract: In order to assess whether electro-acupuncture (EA) can reduce a high uterine artery blood flow impedance, 10 infertile but otherwise healthy women with a pulsatility index (PI) >=3.0 in the uterine arteries were treated with EA in a prospective, non-randomized study. Before inclusion in the study and throughout the entire study period, the women were down-regulated with a gonadotrophin-releasing hormone analogue (GnRHa) in order to exclude any fluctuating endogenous hormone effects on the PI. The baseline PI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(138 citation statements)
references
References 22 publications
5
128
0
5
Order By: Relevance
“…In our study, ovarian artery velocitometry parameters were not significantly different between BD patients and controls. Uterine artery velocimetry indexes, such as RI, PI and S/D, are usually important in pregnancy (19,20), but they were considered also valuable in the assessment of endometrial receptivity (21). Our results revealed that uterine artery Doppler parameters were similar to controls.…”
Section: Original Papersupporting
confidence: 59%
“…In our study, ovarian artery velocitometry parameters were not significantly different between BD patients and controls. Uterine artery velocimetry indexes, such as RI, PI and S/D, are usually important in pregnancy (19,20), but they were considered also valuable in the assessment of endometrial receptivity (21). Our results revealed that uterine artery Doppler parameters were similar to controls.…”
Section: Original Papersupporting
confidence: 59%
“…It is being thought that severe military conflicts in Africa shorten the expected lifetime for more than 2 years. In general, WHO had calculated that 269 thousand people had died in 1999 due to the effect of wars and that loss of 8.44 million healthy years of life had occurred (2,3). Wars negatively affect the provision of health services.…”
Section: War and Women's Healthmentioning
confidence: 99%
“…Досвід традиційної східної медицини, під-тверджений результатами наукових дослід-жень рефлексотерапії, свідчить про можливість використання в сучасних репродуктивних тех-нологіях акупунктури [5,6]. Згадані дослід-ження довели, що акупунктурна стимуляція біологічно активних точок здатна активувати в структурах центральної нервової системи (ЦНС) продукцію та секрецію багатофункціо-нальних нейромодуляторів -ендоморфінів.…”
Section: аналіз літературних даних та постановка завдання дослідженняunclassified